Identifying SARS-CoV-2 antiviral compounds by screening for small molecule inhibitors of Nsp5 main protease. Issue 13 (16th July 2021) - Milligan, Jennifer C.; Zeisner, Theresa U.; Papageorgiou, George; Joshi, Dhira; Soudy, Christelle; Ulferts, Rachel; Wu, Mary; Lim, Chew Theng; Tan, Kang Wei; Weissmann, Florian; Canal, Berta; Fujisawa, Ryo; et al.
Abstract : The coronavirus 2019 (COVID-19) pandemic, caused by the severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2), spread around the world with unprecedented health and socio-economic effects for the global population. While different vaccines are now being made available, very few antiviral drugs have been approved. The main viral protease (nsp5) of SARS-CoV-2 provides an excellent target for antivirals, due to its essential and conserved function in the viral replication cycle. We have expressed, purified and developed assays for nsp5 protease activity. We screened the nsp5 protease against a custom chemical library of over 5000 characterised pharmaceuticals. We identified calpain inhibitor I and three different peptidyl fluoromethylketones (FMK) as inhibitors of nsp5 activity in vitro, with IC50 values in the low micromolar range. By altering the sequence of our peptidomimetic FMK inhibitors to better mimic the substrate sequence of nsp5, we generated an inhibitor with a subnanomolar IC50 . Calpain inhibitor I inhibited viral infection in monkey-derived Vero E6 cells, with an EC50 in the low micromolar range. The most potent and commercially available peptidyl-FMK compound inhibited viral growth in Vero E6 cells to some extent, while our custom peptidyl FMK inhibitor offered a marked antiviral improvement.